Künstliche Intelligenz und professionsbezogene Aufgaben von Lehrkräften - Herzig, Bardo (SchulVerwaltung Bayern)

Team-Teaching angehender Lehrkräfte und Kompetenzen von Kindern im inklusiven naturwissenschaftlichen Sachunterricht. Vortrag auf der Tagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“, Sektion Schulpädagogik, Deutsche Gesellschaft für Erziehungswissenschaft (DGfE). Thema: „Bildung ohne Grenzen denken. Visionen der Grundschulbildung im europäischen Raum" - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Einstellungen und prosoziales Verhalten von Grundschulkindern gegenüber Peers mit emotional-sozialem Förderbedarf im inklusiven Unterricht. Vortrag auf der Tagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“, Sektion Schulpädagogik, Deutsche Gesellschaft für Erziehungswissenschaft (DGfE). Thema: „Bildung ohne Grenzen denken. Visionen der Grundschulbildung im europäischen Raum" - Löper, Marwin Felix; Hellmich, Frank

Exploring primary school teachers’ and special education teachers’ self-efficacy beliefs concerning inclusive education: A qualitative study. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Finke, Pauline; Schulze, Jan Roland; Hellmich, Frank

The role of teacher feedback for primary school students’ motivation and mathematical competencies. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Finke, Nils; Knickenberg, Margarita; Hellmich, Frank

Pre-service teachers’ professional self-concept development concerning team-teaching in primary schools. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Schulze, Jan Roland; Hellmich, Frank

Metaphors in 24 WIRED Level 5 Videos (Data corpus) - Scharlau, Ingrid; Miriam, Körber

Effects of a cooperation training on inclusion-related self-concepts of pre-service teachers. Poster Presentation. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Feedback as a predictor of primary school students’ motivation and mathematical competence. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Finke, Nils; Knickenberg, Margarita; Hellmich, Frank

Effects of parental feedback on children’s perceived feedback, motivation and achievement. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Knickenberg, Margarita; Hoya, Fabian Karl; Hellmich, Frank

Differences in pre-service teachers’ self-efficacy beliefs and willingness for inclusive education. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Görel, Gamze; Franzen, Katja; Hellmich, Frank

The role of teacher behaviour in students’ attitudes and support towards peers with disabilities. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Löper, Marwin Felix; Hellmich, Frank

Teachers’ self-efficacy beliefs and attitudes concerning inclusive education. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Finke, Pauline; Schulze, Jan Roland; Hellmich, Frank

Explanatory factors for students’ attitudes and their supportive behaviour towards peers with social and emotional disabilities. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Löper, Marwin Felix; Hellmich, Frank

Designing Digital Service Innovation Hubs: An Ecosystem Perspective on the Challenges and Requirements of SMEs and the Public Sector - Schäfer, Jannika Marie; Liebschner, Jonas; Rajko, Polina; Cohnen, Henrik; Lugmair, Nina; Heinz, Daniel (Proceedings of the 20th International Conference on Wirtschaftsinformatik (WI 2025))
Service ecosystems reshape service innovation by enabling value co-creation among diverse actors. However, small and medium-sized enterprises and public organizations face significant challenges navigating and leveraging these ecosystems due to resource constraints, knowledge gaps, and partnership difficulties. While digital innovation hubs have been introduced as potential intermediaries to foster innovation, existing models primarily focus on individual solutions and networking rather than orchestrating service innovation. This study investigates the design of a digital service innovation hub as an orchestrating entity that facilitates service innovation within ecosystems. Under the design science research paradigm, we analyze the challenges faced by small and medium-sized enterprises and public organizations and derive design requirements for these hubs. Based on 17 expert interviews and focus group validations, we define the problem space and provide a requirements catalog for designing digital service innovation hubs as a step towards providing holistic support for service innovation initiatives.
Keywords: service innovation; ecosystem; innovation hubs; SMEs; public sector

The power of combined modalities in interactive robot learning - Beierling, Helen; Beierling, Robin; Vollmer, Anna-Lisa (Frontiers in Robotics and AI)
This study contributes to the evolving field of robot learning in interaction with humans, examining the impact of diverse input modalities on learning outcomes. It introduces the concept of "meta-modalities" which encapsulate additional forms of feedback beyond the traditional preference and scalar feedback mechanisms. Unlike prior research that focused on individual meta-modalities, this work evaluates their combined effect on learning outcomes. Through a study with human participants, we explore user preferences for these modalities and their impact on robot learning performance. Our findings reveal that while individual modalities are perceived differently, their combination significantly improves learning behavior and usability. This research not only provides valuable insights into the optimization of human-robot interactive task learning but also opens new avenues for enhancing the interactive freedom and scaffolding capabilities provided to users in such settings.
Keywords: human-robot interaction; human-in-the-loop learning; reinforcement learning; interactive robot learning; multi-modal feedback; learning from demonstration; preference-based learning; scaffolding in robot learning

Human-Interactive Robot Learning: Definition, Challenges, and Recommendations - Baraka, Kim; Idrees, Ifrah; Faulkner, Taylor Kessler; Biyik, Erdem; Booth, Serena; Chetouani, Mohamed; Grollman, Daniel H.; Saran, Akanksha; Senft, Emmanuel; Tulli, Silvia; Vollmer, Anna-Lisa; Andriella, Antonio; et al. (Transactions on Human-Robot Interaction)
Robot learning from humans has been proposed and researched for several decades as a means to enable robots to learn new skills or adapt existing ones to new situations. Recent advances in artificial intelligence, including learning approaches like reinforcement learning and architectures like transformers and foundation models, combined with access to massive datasets, has created attractive opportunities to apply those data-hungry techniques to this problem. We argue that the focus on massive amounts of pre-collected data, and the resulting learning paradigm, where humans demonstrate and robots learn in isolation, is overshadowing a specialized area of work we term Human-Interactive-Robot-Learning (HIRL). This paradigm, wherein robots and humans interact during the learning process, is at the intersection of multiple fields (artificial intelligence, robotics, human-computer interaction, design and others) and holds unique promise. Using HIRL, robots can achieve greater sample efficiency (as humans can provide task knowledge through interaction), align with human preferences (as humans can guide the robot behavior towards their expectations), and explore more meaningfully and safely (as humans can utilize domain knowledge to guide learning and prevent catastrophic failures). This can result in robotic systems that can more quickly and easily adapt to new tasks in human environments. The objective of this paper is to provide a broad and consistent overview of HIRL research and to guide researchers toward understanding the scope of HIRL, and current open or underexplored challenges related to four themes — namely, human, robot learning, interaction, and broader context. The paper includes concrete use cases to illustrate the interaction between these challenges and inspire further research according to broad recommendations and a call for action for the growing HIRL community
Keywords: Robot learning; Interactive learning systems; Human-robot interaction; Human-in-the-loop machine learning; Teaching and learning

Antiferromagnetic ordering and critical behavior induced giant magnetocaloric effect in distorted kagome lattice Gd3BWO9 - Wang, Zhuoqun; Cui, Xueling; Treu, Tim; Guo, Jiesen; Liu, Xinyang; Klinger, Marvin; Heil, Christian; Ma, Nvsen; Sheng, Xianlei; Deng, Zheng; Lu, Xingye; Wang, Xiancheng; et al. (Physical Review Materials)

Demonstration of domain wall current in MgO-doped lithium niobate single crystals up to 400°C - Wulfmeier, Hendrik; Yakhnevych, Uliana; Boekhoff, Cornelius; Diima, Allan; Kunzner, Marlo; Verhoff, Leonard M.; Paul, Jonas; Ratzenberger, Julius; Beyreuther, Elke; Gössel, Joshua; Kiseleva, Iuliia; Rüsing, Michael; et al. (Solid State Ionics)
Conductive ferroelectric domain walls (DWs) represent a promising topical system for the development of nanoelectronic components and device sensors to be operational at elevated temperatures. DWs show very different properties as compared to their hosting bulk crystal, in particular with respect to the high local electrical conductivity. The objective of this work is to demonstrate DW conductivity up to temperatures as high as 400 °C which extends previous studies significantly. Experimental investigation of the DW conductivity of charged, inclined DWs is performed using 5 mol % MgO-doped lithium niobate single crystals. Current–voltage ( ) curves are determined by DC electrometer measurements and impedance spectroscopy and found to be identical. Moreover, impedance spectroscopy enables to recognize artifacts such as damaged electrodes. Temperature dependent measurements over repeated heating cycles reveal two distinct thermal activation energies for a given DW, with the higher of the activation energies only measured at higher temperatures. Depending on the specific sample, the higher activation energy is found above 160 °C to 230 °C. This suggests, in turn, that more than one type of defect/polaron is involved, and that the dominant transport mechanism changes with increasing temperature. First principles atomistic modeling suggests that the conductivity of inclined domain walls cannot be solely explained by the formation of a 2D carrier gas and must be supported by hopping processes. This holds true even at temperatures as high as 400 °C. Our investigations underline the potential to extend DW current based nanoelectronic and sensor applications even into the so-far unexplored temperature range up to 400 °C.

Second harmonic generation contrasts of ferroelectric domain structures and composition in lithium niobate–tantalate mixed crystals - Koppitz, Boris; Saxena, Tanya; Bernhardt, Felix; Ganschow, Steffen; Sanna, Simone; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Lithium niobate–tantalate mixed (LNT) crystals promise improved performance and new applications for optical, piezomechanical, or electrical devices when compared to the end composition compounds lithium niobate and lithium tantalate. The macroscopic properties of ferroelectrics highly depend on the structure of the underlying ferroelectric domains, which within mixed crystals can interact with the local changes in chemical compositions. In this work, we demonstrate how ferroelectric domain walls can unambiguously be identified and distinguished from local changes in composition by correlating piezoresponse force microscopy with second harmonic generation microscopy, using the Cherenkov contrast, reference crystal contrast, and negative phase mismatching contrast. We demonstrate how measuring the associated intensity change when approaching negative phase mismatching can be used to deduce the local tantalum concentration fast and over a large sample area. Based on these results, we study the natural domain structures that appear from Czochralski-grown, multi-domain LNT solid solution crystals. The developed results and methods serve as the central foundation to poling these mixed crystal systems and are key for their integration and applications.